2007
DOI: 10.1017/s0269964807000290
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Assignment of Dedicated and Flexible Servers in Tandem Lines

Abstract: Consider a system of queuing stations in tandem having both flexible servers (who are capable of working at multiple stations) and dedicated servers (who can only work at the station to which they are dedicated). We study the dynamic assignment of servers to stations in such systems with the goal of maximizing the long-run average throughput. We also investigate how the number of flexible servers influences the throughput and compare the improvement that is obtained by cross-training another server (i.e., incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 35 publications
2
30
0
Order By: Relevance
“…However, the threshold value where the moving server switches from station 1 to station 2 now also depends on the status of the other servers. For longer tandem lines with generalist servers, Andradóttir, Ayhan, and Down [4] showed that any non-idling server assignment policy is optimal. We generalize this result and prove that any non-idling policy (in which servers idle only when they are down) is still optimal when the servers are subject to failures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the threshold value where the moving server switches from station 1 to station 2 now also depends on the status of the other servers. For longer tandem lines with generalist servers, Andradóttir, Ayhan, and Down [4] showed that any non-idling server assignment policy is optimal. We generalize this result and prove that any non-idling policy (in which servers idle only when they are down) is still optimal when the servers are subject to failures.…”
Section: Introductionmentioning
confidence: 99%
“…In the interest of space, we do not provide a complete literature review here, but refer the interested reader to Hopp and Van Oyen [13] for a comprehensive review of the literature in this area, and to Akşin, Armony, and Mehrotra [4], Akşin, Karaesmen, andÖrmeci [5], and Gans, Koole, and Mandelbaum [12] for thorough reviews of the literature on flexible servers in call centers. This paper is most closely related to other works that employ Markov decision process techniques and sample path analysis in determining effective server allocation schemes, see for example Ahn, Duenyas, and Zhang [1], Ahn and Lewis [2], Ahn and Righter [3], Andradóttir and Ayhan [6], Andradóttir, Ayhan, and Down [7,8], Kaufman, Ahn, and Lewis [15],Örmeci [17], Sennott, Van Oyen, and Iravani [19], Van Oyen, Gel, and Hopp [20], and Wu, Lewis, and Veatch [21]. However, these papers only consider cases where the combined rate of a set of collaborating servers is additive (i.e., α = 1).…”
Section: Introductionmentioning
confidence: 84%
“…Sennott et al [15] analyze tandem production lines with multiple servers, dedicated servers The work most closely related to this paper involve maximizing throughput in tandem queues. Apart from [2] and [3] which are described in detail above, Andradottir et al also investigated tandem lines with flexible and dedicated servers [6], failure prone servers [7], and synergistic servers [8]. Kirkizlar et al [12] analyze a tandem production line which is understaffed, i.e., there are more stations than servers.…”
Section: Introductionmentioning
confidence: 99%